Electromyographic activity of quadriceps muscle during sit-to-stand in patients with unilateral knee osteoarthritis - Hamad S. Al Amer; Mohamed A. Sabbahi; Hesham N. Alrowayeh; William J. Bryan; Sharon L. Olson (BMC Research Notes, 2018)
Abstract Objective The sit-to-stand (STS) is a simple test to evaluate the functional performance of the quadriceps muscle in patients with knee osteoarthritis (OA). The aim was to evaluate the electromyographic (EMG) activity of the ipsilateral quadriceps during STS task at different seat heights and feet positions in patients with severe unilateral OA. The EMG activity was recorded in a group of eight participants with unilateral OA during the performance of STS task in four conditions: (1) knee-height seat with feet together, (2) knee-height seat with feet askew (feet side by side and heel-to-toe), (3) low-height seat (25% lower than knee-height seat) with feet together, and (4) low-height seat with feet askew. Results There was a statistically significant difference among the four conditions in the EMG activity (p =0.004). Particularly, the EMG activity of the quadriceps was significantly higher when participants rose from the low height with their feet askew than when they rose from the knee height with their feet placed together (p =0.004) or askew (p =0.002). These results recommend considering initial feet position and seat height when evaluating the functional activity of the quadriceps in patients with unilateral OA using STS test.